(untitled) (International Journal of Physiotherapy, 2025)
Background: Posture is a dynamic determinant of systemic health, influencing structural alignment, physiological regulation, biomechanical efficiency, psychological well-being, and social interaction. Despite its pervasive role, posture remains underrepresented in mainstream clinical and public health discourse. Methods: This narrative review synthesizes evidence across anatomical foundations, physiological mechanisms, biomechanical consequences, pain syndromes, psychosocial correlates, and intervention strategies to highlight posture’s multisystem impact. A comprehensive literature search was conducted using PubMed, Scopus, Google Scholar, and ScienceDirect databases for studies published between 2010 and 2025. Keywords related to posture and health were applied across disciplines, and thematic synthesis was used to organize findings into interconnected domains. Results: Results indicate that postural alignment affects musculoskeletal integrity, respiratory and circulatory function, neural signalling, and emotional regulation. Deviations from neutral posture contribute to chronic pain, energy inefficiency, functional limitations, and psychological distress. Conclusion: Evidence supports the clinical efficacy of interventions such as postural education, therapeutic exercise, ergonomic modifications, and interdisciplinary care. Recognizing posture as a multifactorial indicator of health may enhance prevention, rehabilitation, and overall well-being. Future research should prioritize culturally sensitive, longitudinal, and personalized approaches to postural assessment and intervention.